STUDI ETOLOGI SEMUT RANGRANG (OECOPHYLLA SMARAGDINA) PADA KONDISI HABITAT YANG BERBEDA - Zebua , Ester Novi Kurnia (Universitas Nias Raya, 2022)
. Sources of data in this study is primary data obtained directly in the field through interviews, observations and documentation. While secondary data obtained from other sources such as books, journals, and articles made by other people. The method used in this research is explorative ethology with a descriptive qualitative approach. Data collection techniques in this study were observation, interviews and documentation. The data analysis technique in this research is to use data reduction techniques, data presentation and conclusion drawing. The technique of checking the validity of the data in this study uses source triangulation. The research findings obtained by the researchers in this study are that weaver ants are more commonly found in arboreal habitats than in terrestrial habitats, there are differences in the ethology of weaver ants in terrestrial habitats and weaver ants in arboreal habitats. The ethological differences in question are mating ethology, feeding ethology, self-defense ethology, communication ethology and weaver ant ecology. Researchers suggest in this study that further researchers can further develop research on insect ethology, especially the weaver ant species so that this research can be used as reference material in teaching insect behavior, as a guide and reading for those in need and as a source of information and knowledge about the roles and benefits. weaver ants in agriculture.